2022
DOI: 10.1007/s10803-022-05511-4
|View full text |Cite|
|
Sign up to set email alerts
|

Spoken Language Change in Children on the Autism Spectrum Receiving Community-Based Interventions

Abstract: We assessed the spoken language of 73 preschool aged children on the autism spectrum receiving community-based early intervention at two time points, approximately 7 months apart. Using the Spoken Language Benchmarks, there was a small non-significant change in the proportion of children transitioning from below, to at or above, Phase 3 (word combinations). Using binomial regression, a model comprising seven of nine clinician-proposed child-related predictors explained 64% of the variance. None of the predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our study found a similar pattern when examining the longitudinal relation between child factors at T1 and our NLS‐derived measures at T2. Exploring child factors that predict changes in URate and CTRate aids in tailoring goals to children's individual needs and strengths (Trembath et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study found a similar pattern when examining the longitudinal relation between child factors at T1 and our NLS‐derived measures at T2. Exploring child factors that predict changes in URate and CTRate aids in tailoring goals to children's individual needs and strengths (Trembath et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although not characterized by the current study, stakeholder input would motivate future research. Employing a supportive and collaborative framework with multiple stakeholders in research can provide a stronger empirical base with direct relevance to clinical practice and translational applications (Trembath et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We characterized each child's language phase using expressive language benchmarks developed by experts assembled by the National Institute on Deafness and Other Communication Disorders (Tager-Flusberg et al, 2009). These benchmarks use a developmental framework to provide uniform terminology for describing expressive language in children with autism and have proved to be useful for investigating variables related to children's language growth (Ellawadi & Weismer, 2015;Trembath et al, 2022). The guidelines of Tager-Flusberg and colleagues ( 2009) denote that language phases may be determined using multiple sources including language samples collected during administration of semistructured direct assessment measures.…”
Section: Aim 2 Exploring Pvr By Language Phasementioning
confidence: 99%
“…59 As previously identified in the literature, children with ASD may benefit more from interventions if they begin at a younger age, although more needs to be understood regarding the interactions between predictor variables. [60][61][62] The finding of younger age predicting greater improvements following intervention also highlights the importance of continuing research on expressive and receptive communication in ASD in preschool children.…”
mentioning
confidence: 96%